THE QUALITY OF CHICKEN EGG FED RATION CONTAINING FERMENTED NON-CONVENTIONAL FEED - Sudrajat, D; Priytana, F; Nur, H (Jurnal Pertanian, 2019)
Non-conventional feeds are generally of low quality so feed fermentation needs to be done to increase its use. This research was conducted to examine the effect of giving fermented feed types on egg quality. This research was conducted in June until August 2018 in the cage of Cibadak poultry in Sukabumi district. The animals used in this study were 24 Brown Strain Isa Brown laying hens as many as 24 birds. The study used a completely randomized design (CRD) consisting of 6 treatments and 4 replications. The treatment in this study was R0 = 100% Basic Ration, R1 = 90% Basic ration + 10% fermented non conventional ration, R2 = 80% Basic ration + 20% fermented non conventional ration, R3 = 70% Basic ration + 30% Non ration conventional fermented, R4 = 60% Basic ration + 40% Fermented non-conventional ration, R5 = 50% Basic ration + 50% Fermented non-conventional ration. The data obtained were analyzed using Analysis of variance (ANOVA), if the data showed results that were significantly different (P <0.05) followed by the Duncan test. The results showed that substitution feeding did not significantly influence the egg index, egg white weight, Haugh Unit value, and shell thickness. Therefore, it can be concluded that demonstrable non-conventional feed can be given in ration of laying hens up to 50%.